Stress in the USSR. On the Dissemination of Health Knowledge in the Soviet Public Sphere, 1960s–1991 Jan Arend - Arend, Jan (Comparativ, 2019)
When and where does “stress” – a psychological and bodily condition associated with the pressure to perform – become a social concern? Previous historical research has situated the topic in the West, linking it to what is understood to be a Western type of capitalism and / or neoliberalism. This article departs from this line of research by demonstrating the broad dissemination of the topic of stress in the Soviet public sphere since the mid-1960s. Based on an examination of three of the most widely read Soviet state newspapers, the article shows how the notion of stress was conveyed to the Soviet public and thereby sheds light on the circulation of knowledge related to health in the period of late socialism. Stress, although the concept originally came to the Soviet context through a process of knowledge transfer from the West, had a life of its own in the Soviet Union. By analyzing how the concept of stress was adapted to a state socialist context, the article points to previously underexplored cross-bloc similarities with regard to perceptions of emotions and the body.